Analisis Sentimen Ulasan Aplikasi Gojek Menggunakan Support Vector Machine Dan Random Forest - Aditya, Azka Bima; Samsudin, Syafri; Rizki, Winahyu Pandu; Mahendra, Mahir; Setiawan, Arif (LPPM STT Terpadu Nurul Fikri, 2025)
The rapid development of digital transportation, such as Gojek, requires a deep understanding of user satisfaction. This study analyzes the sentiment of Gojek application reviews to evaluate public opinion and compare the performance of the Support Vector Machine (SVM) and Random Forest models. A quantitative experimental method was applied to 30,055 user reviews for versions